Design of Efficient Bifunctional Oxygen Reduction/Evolution Electrocatalyst: Recent Advances and Perspectives. Issue 23 (14th July 2017) - Huang, Zhen‐Feng; Wang, Jiong; Peng, Yuecheng; Jung, Chi‐Young; Fisher, Adrian; Wang, Xin
Abstract: Oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are the two most important reactions in rechargeable metal‐air battery, a promising technology to meet the energy requirements for various applications. The development of low‐cost, highly efficient and stable bifunctional ORR/OER catalysts is critical for a large‐scale application of this technology. In this review, the authors first introduce the fundamentals of bifunctional ORR/OER electrocatalysis in alkaline electrolyte. Various types of nanostructured materials as bifunctional ORR/OER catalysts including metal oxide, hydroxide and sulfide, functional carbon material, metal, and their composites are then reviewed. The crucial factors that can be used to tune the activity of the catalyst towards ORR/OER are summarized, including (1) phase, morphology, crystal facet, defect, mixed‐metal and strain engineering for metal oxide; (2) heteroatom doping, topological defects, and formation of metal‐N‐C structure for carbon material; (3) alloy effect for metal. These experiences lay the foundation for large scale application of metal‐air battery and can also effectively guide the rational design of catalysts for other electrocatalytic reactions. Abstract : Recent progress on the design and synthesis of bifunctional oxygen reduction/evolution electrocatalysts used in alkaline electrolyte is reviewed. Various types of nanostructured catalysts including metal oxide, hydroxide and sulfide, functional carbon material, metal, and their composites, are presented. The crucial factors determining the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) performance are also summarized.